Correcting Working Postures in Water Pump Assembly Tasks using the OVAKO Work Analysis System (OWAS) - Ketan, Hussein S.; Al-Zuheri, Atiya Kadhim (Al-Khwarizmi Engineering Journal, 2008)
Ovako Working Postures Analyzing System (OWAS) is a widely used method for studying awkward working postures in workplaces. This study with OWAS, analyzed working postures for manual material handling of laminations at stacking workstation for water pump assembly line in Electrical Industrial Company (EICO) / Baghdad. A computer program, WinOWAS, was used for the study. In real life workstation was found that more than 26% of the working postures observed were classified as either AC2 (slightly harmful), AC3 (distinctly harmful). Postures that needed to be corrected soon (AC3) and corresponding tasks, were identified. The most stressful tasks observed were grasping, handling, and positioning of the laminations from workers. The construction of real life workstation is modified simultaneously by redesign suggestions in the values of location (positioning) factors for stacking workstation. The simulation workstation executed by mean of parametric CAD software. That modifications lead to improvement in the percentage of harmful postures. It was therefore recommended the use of supplementary methods is required to identify ergonomic risk factors for handling work or other hand-intensive activities on industry sites.